Sustainable Household Waste Management Arrangements - Ni Wayan Eka Sumartini (IAHN-TP Palangka Raya, 2024)
The increase in population has an impact on the increase in the amount of waste. The large amount of waste mainly comes from household activities in fulfilling the needs ofhuman life. The accumulation of large amounts of waste has a negative impact onenvironmental health, so it needs proper management. The management of householdwaste and waste similar to household waste has been regulated by the governmentthrough Government Regulation No. 81 of 2012 concerning Management ofHousehold Waste and Waste Similar to Household Waste. For this reason, this study aims to analyze the regulation of waste management, especially household waste andwaste similar to household waste. The normative legal research method used in thisresearch and uses a statutory approach. The results of this study show that householdwaste management regulations have not been regulated in detail, and enforcement isalso very weak because there are no clear sanctions against violations committed. The regulation of household waste management has an impact on the management ofhousehold waste and similar household waste in the form of reduced waste generationand waste shipments to landfills.